Performance of beamforming combined with spacetime- frequency code in spatially correlated channel. (1st January 2014) - Shrivastava, Neeraj; Trivedi, Aditya
Multiple antennas can be used in wireless systems to achieve good quality of service and high data rate communication. Recently, efficient Space-Time-Frequency (STF) codes have been developed to improve the diversity gain. In this paper, we propose an approach to improve Bit Error Rates (BER). Our approach incorporates beamforming and STF coding. The proposed beamforming combined with STF code offers significant improved performance over STF. Simulation results reveal significant gain improvement over STF. The proposed scheme offers significant improved performance over STF. For the BER of 10 –3, it gives a gain of approximately 3.0 dB over STF without beamforming scheme. It is observed that the proposed scheme gives better performance as compared to the combined Space-Time Block Code (STBC) with beamforming. It gives a gain of approximately 6.0 dB over this scheme. We also calculate the decoding complexity of the proposed scheme over combined STBC with beamforming. It is seen that this approach improves the BER of the system with the same computational complexity.